2022
DOI: 10.1101/2022.07.12.499605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Association Study in a Rat Model of Temperament Identifies Multiple Loci for Exploratory Locomotion and Anxiety-Like Traits

Abstract: Common genetic factors likely contribute to multiple psychiatric diseases including mood and substance use disorders. Certain stable, heritable traits reflecting temperament, termed externalizing or internalizing, play a large role in modulating vulnerability to these disorders. To model these heritable tendencies, we selectively bred rats for high and low exploration in a novel environment (bred High Responders (bHR) vs. Low Responders (bLR)). To identify genes underlying the response to selection, we phenoty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…Thus, a higher percent of females than males were classified as ST versus GT (Fig Notably, although many of these behaviors were influenced by sex (discussed above), including sex in the model did not appear to modulate the relationships between behavioral variables (all sex interaction terms p>0.164) or fully explain those relationships (all behavioral relationships still had p<0.0284). The re-creation of correlations between bHR/bLR phenotypical behaviors in a subset of the F2 generation imply a shared etiology for these behaviors, including environmental and genetic influences, and is consistent with the phenotypical and genetic correlations of the whole F2 cohort from our GWAS findings (Chitre et al, 2022). shown previously to have bHR/bLR differences in (Flagel et al, 2010)).…”
Section: The Bhr/blr (F0) Cross-breeding Scheme Produced F2 Animals W...supporting
confidence: 89%
See 4 more Smart Citations
“…Thus, a higher percent of females than males were classified as ST versus GT (Fig Notably, although many of these behaviors were influenced by sex (discussed above), including sex in the model did not appear to modulate the relationships between behavioral variables (all sex interaction terms p>0.164) or fully explain those relationships (all behavioral relationships still had p<0.0284). The re-creation of correlations between bHR/bLR phenotypical behaviors in a subset of the F2 generation imply a shared etiology for these behaviors, including environmental and genetic influences, and is consistent with the phenotypical and genetic correlations of the whole F2 cohort from our GWAS findings (Chitre et al, 2022). shown previously to have bHR/bLR differences in (Flagel et al, 2010)).…”
Section: The Bhr/blr (F0) Cross-breeding Scheme Produced F2 Animals W...supporting
confidence: 89%
“…Both genes have also been found to be differentially expressed in the hippocampus of other rat models with resilience to internalizing-like tendencies (Blaveri et al, 2010;Meckes et al, 2018). Mfge8 is located close to behavioral QTLs in both our F2 GWAS and exome sequencing study (Chitre et al, 2022;Z. Zhou et al, 2019), whereas Fcrl2 is not found in a region implicated by our genetic studies.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations